Longitudinal association between parental-to-child-Maltreatment and self-reported Generalized Anxiety Disorder symptoms in Pakistani Adolescents - Maryam Pyar Ali Lakhdir; Ghazal Peerwani; Salman Muhammad Soomar; Apsara Ali Nathwani; Salima Farooq; Naureen Akber Ali; Asif Khaliq; Muhammad Masood Kadir; Syed Iqbal Azam (BMC, 2021)
Abstract Background Parent-to-child maltreatment is considered one of the risk factors for Generalized Anxiety Disorder (GAD) symptoms, but this hypothesis has not been adequately tested in Pakistani settings. Aim This study aimed to examine the association between parent-to-child maltreatment and the risk of developing GAD symptoms among adolescents. Methods The association of none to rare, occasionally, and frequently parent-to-child maltreatment with the incidence of GAD symptoms was investigated in a sample of 800 adolescents aged 11-17 years who were followed for two years. Parent-to-child maltreatment was assessed using ICAST-C (International child abuse screening tool). GAD Symptoms were determined by SCARED (Screen for children anxiety-related disorders). Cox Proportional Algorithm was used to estimate risk ratios. Results Among children with both uneducated parents, frequently maltreatment was associated with 7.31 (2.20-24.04) times the risk of GAD symptoms compared to none to rare maltreatment. In contrast, the risk of GAD symptoms in frequently maltreated children was 5.58 times (1.40-21.97) than negligibly maltreated children with either educated parent. Conclusion The frequency of parent-to-child maltreatment is significantly associated with an increased risk of developing GAD symptoms in which parental education plays a crucial role. Parents should be imparted with the awareness of the consequences of child maltreatment. In Pakistani settings the need to have this awareness is even more necessary due to the culturally acceptable disciplinary measures used by parents.